(untitled) (Journal of Current Biomedical Research, 2023)
Kaposi Sarcoma KS is a rare, borderline vascular tumour that affects the mucocutanous surfaces, and lymph nodes and visceral organs occasionally. Various forms have been described with a common association with Herpes Simplex virus 8 infection, although immunological, environmental and Kaposi Sarcoma KS is a rare, borderline vascular tumor that affects the muco-cutanous surfaces, and lymph nodes and visceral organs occasionally. Various forms have been described with a common association with Herpes Simplex virus 8 infection, although immunological, environmental and genetic factors play significant role in its pathogenesis. Urogenital involvement is uncommon and isolated scrotal KS in HIV negative individuals is extremely rare. We therefore report the 5th of such case in English literature, involving a 65 year old Nigerian, with confirmed histological and immunohistochemistry diagnostic features. Patient underwent surgical excision of the lesion and is being considered for chemotherapy. genetic factors play significant role in its pathogenesis. Urogenital involvement is uncommon and isolated scrotal KS in HIV negative individuals is extremely rare. We therefore report the 5th of such case in English literature, involving a 65 year old Nigerian, with confirmed histological and immunohistochemistry diagnostic features. Patient underwent surgical excision of the lesion and is being considered for chemotherapy.